2020
DOI: 10.3390/ijerph17051593
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Body Image, Disordered Eating and Lifestyle on the Quality of Life in Lithuanian University Students

Abstract: Purpose. The present study aimed to explore the associations between body image concerns (BI), disordered eating (DE), health-related lifestyle, and the different domains of the quality of life (QoL) in a Lithuanian sample of student-aged men and women. Methods. A mixed-gender sample of students (N = 1850, 58.8% were women, average age 21.6 ± 5.0 years) completed a series of questionnaires, including health-related lifestyles, BI, DE, and QoL. A series of simultaneous multiple linear regression analyses were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 47 publications
(77 reference statements)
1
13
0
1
Order By: Relevance
“…There were no mean age and BMI differences between the intervention and control groups. The BMI, leisure-time exercise, body image concerns, disordered eating scores were very similar to the mean scores that were reported in previous research with a large Lithuanian student sample [36].…”
Section: Participantssupporting
confidence: 85%
See 1 more Smart Citation
“…There were no mean age and BMI differences between the intervention and control groups. The BMI, leisure-time exercise, body image concerns, disordered eating scores were very similar to the mean scores that were reported in previous research with a large Lithuanian student sample [36].…”
Section: Participantssupporting
confidence: 85%
“…Our sample represented healthy young women with low body image concerns that reflect the tendencies which were observed in other large samples of Lithuanian female students [ 36 , 41 ]. At baseline, we found no significant differences between intervention and control groups except for a higher level of perceived media pressures and lower physical activity level in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Apacio-Martienz et al [ 49 ] showed that disordered eating attitudes were strongly linked to self-esteem, body image, the desired body, and the use of social media, especially among female subjects. Baceviciene et al [ 66 ] identified the relationship between satisfaction with body image and quality of life among college students. Ansari et al [ 67 ] pointed out that high BMI and depressive symptoms were found more often among students dissatisfied with their weight.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have noted that human health can be affected by a combination of factors, including the living environment [ 74 , 75 , 76 , 77 ]. Upon moving from across the country to the place of their study, students need to adapt to a new climatic and social environment [ 78 ].…”
Section: Discussionmentioning
confidence: 99%